The Qur'an and the Sunnah The Time-Space Factor - Al-Alwani, Taha Jabir (International Institute of Islamic Thought, 1995)
For too long now, the Qur'an and the Sunnah, great sources of strength, purity, knowledge and inspiration for the Ummah, have not been adequately tapped. Skirting their peripheries or overdwelling on one or two of their multifarious facets and tributaries has done a disservice to the immense potential of the fountainhead, while denying the Ummah indeed the whole world innumerable benefits from them. Now that the Ummah is becoming increasingly aware of its own problems as well as latent powers, and yearns to revive its leading role in the forging of history and civilization, the issue of drawing on the wellspring becomes more relevant and urgent. Revisiting these two sources is no longer a scholastic, academic, nostalgic, or escapist indulgence, but a great journey of discovery that promises untold rewards. Paradoxically, the journey through the resplendent pages of the Qur'an and the Sunnah to a time and place in the past should yield a more mature awareness of the dynamics of social and historical change and a human being's role on earth, honing and sharpening the Muslims' capacity to deal with the demands of the present moment and the challenges of the future. Suggestions for a new reading of the Qur'an and the Sunnah have been put forward from Islamic and other angles in the recent years. In this book Dr. Al-Alwani and Dr. Khalil, two well-known Muslim thinkers, contribute their views for a proper approach to these sources from within the Islamic framework.